Growth Response to a Scientific Feeding Intervention in Fattening Male Murrah Buffalo Crossbreds under Field Conditions in Kerala, India - , GANESH RAM JAT, GIGGIN T, SMITHA S (Archives of Current Research International, 2025)
Buffaloes rearing play a vital role in India’s rural economy, contributing significantly to milk and meat production. While buffalo milk has received considerable policy and research attention, the rising demand for buffalo meat, particularly from male buffaloes necessitates focus on growth optimisation. In Kerala, where smallholder systems dominate, buffalo meat production remains limited and often constrained by inadequate and imbalanced feeding practices, leading to poor growth and economic returns. This study assessed the impact of a scientifically formulated feeding intervention on the growth performance of Murrah crossbred male buffaloes raised for meat in Thrissur, Kerala. A total of 28 animals were enrolled, of which 24 were retained for analysis after excluding extreme outliers. Over a 60-day period, buffaloes were maintained under uniform management conditions with a total mixed ration (TMR) containing 18% crude protein. Body weight was estimated using Shaeffer’s formula, and average daily gain (ADG) was calculated. A paired t-test was conducted to assess statistical significance. The initial mean body weight was 181.92 ± 9.81 kg, increasing to 202.28 ± 8.32 kg post-intervention (p = 0.0068). The average gain was 20.36 ± 6.85 kg, with an ADG of 0.34 kg/day. Approximately 87.5% of the buffaloes demonstrated positive weight gain, indicating the effectiveness of the feeding strategy. The results confirmed that short-term, scientific nutritional interventions can significantly enhance weight gain in male buffaloes under field conditions. Wider adoption of standard feeding protocols, combined with farmer education and extension support, could improve meat productivity and profitability in smallholder systems.